Antimicrobial Activity of Synthesized Multi-Metallic Nanoparticles using Traditional Indian Siddha Method - Balakrishnan, Kaviarasu; Arumugam, Sivabalan; Ezhumalai, Dhineshkumar; Karthikeyan, Ramasamy; Magesan, G.N. (Asian Journal of Chemistry, 2022)
In present work, multi-metallic nanoparticles were synthesized by chemical method in a controlled environment by using silver, lead, mercury, egg shell powder (contains 1% calcium phosphate, 1% magnesium carbonate, 94% calcium carbonate and 4% organic matter), potassium nitrate, potassium alum and extracts of citrus lemon by following the process defined in Traditional Indian Medicine, Siddha System of Medicine. The morphology, compositions and structure of the product were characterized by powder X-ray diffraction (PXRD), Fourier transform infrared (FTIR), scanning electron microscopy (SEM), energy dispersive X-ray (EDX) and transmission electron microscopy (TEM) techniques. Highly uniform spherical multi-metallic nanoparticle was subjected for the antibacterial activities. The particles were agglomerated as observed by SEM micrographs. The particles were homogeneous, spherical in shape and loosely agglomerated as seen by TEM pictures. The antibacterial activity of the synthesized multi-metallic nanoparticles against B. cereus, S. aureus, E. coli and P. aeuroginosa was demonstrated using the zone of inhibition technique. The synthesized multi-metallic nanoparticle can find plausible biological applications.